1996
DOI: 10.3171/jns.1996.85.5.0772
|View full text |Cite
|
Sign up to set email alerts
|

Is “unilateral” moyamoya disease different from moyamoya disease?

Abstract: Whether a diagnosis of moyamoya disease is justified in patients with typical angiographic evidence of moyamoya disease unilaterally and normal angiographic findings contralaterally remains controversial. In this study the authors analyzed longitudinal angiographic change, familial occurrence, and basic fibroblast growth factor (bFGF) concentration in the cerebrospinal fluid (CSF) of patients with "unilateral" moyamoya disease. Over a 10-year period, 10 cases of unilateral moyamoya disease were followed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 19 publications
4
45
0
Order By: Relevance
“…13,16,20 Several studies have suggested that an association exists between MMD and autoimmune diseases, including Type 1 diabetes mellitus, AIG, SLE, APAS, APS, PBC, GD, and HT. 2,7,15,17,18,20,22,23,25 Furthermore, several reports have demonstrated that thyroid autoantibodies may be associated with the moyamoya development. 13,15,16 Our study also indicated that autoimmune abnormalities may be associated with pathophysiological mechanisms of moyamoya vasculopathy formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,16,20 Several studies have suggested that an association exists between MMD and autoimmune diseases, including Type 1 diabetes mellitus, AIG, SLE, APAS, APS, PBC, GD, and HT. 2,7,15,17,18,20,22,23,25 Furthermore, several reports have demonstrated that thyroid autoantibodies may be associated with the moyamoya development. 13,15,16 Our study also indicated that autoimmune abnormalities may be associated with pathophysiological mechanisms of moyamoya vasculopathy formation.…”
Section: Discussionmentioning
confidence: 99%
“…7,11,14,18 MMD has been reportedly associated with various entities. 2,8,9,13,16,24 Analysis of the coexisting diseases that occur with moyamoya may be helpful in exploring moyamoya pathogeneses.…”
mentioning
confidence: 99%
“…The possibility of progression in adolescence and beyond appears to be infrequent (4,5). The level of basic fibroblast growth factor in the cerebrospinal fluid is reported to be related to progression (6). It thus is reasonable to consider that the presence of unilateral moyamoya vessels in elderly individuals is attributable to atherosclerosis and that this phenomenon is distinct from moyamoya disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moyamoya disease (MMD) is a rare bilateral steno occlusion of the internal carotid artery (ICA) (4), and it is an essential criterion on conventional angiography for the diagnosis (8). The disease mostly occurs in Japanese, Asians and nonCaucasians (3).…”
Section: Introductionmentioning
confidence: 99%